Respostas
respondido por:
4
Regra distributiva:
3a multiplica 3a, depois 3a multiplica -1 e por aí vai...
9a²-3a-3a+1=
9a²-6a+1
3a multiplica 3a, depois 3a multiplica -1 e por aí vai...
9a²-3a-3a+1=
9a²-6a+1
RenatoFerreira111:
Aí depois é só fazer forma de bhaskara?
respondido por:
2
( 3a - 1 ).(3a - 1) = (3a - 1 )² = 3².a² - 2.3a.1 + 1² = 9a² - 6a + 1 pode ser resolvido assim também:
(3a - 1)(3a - 1) = 3a.3a - 3a.1 - 1.3a + 1.1 = 9a² - 6a + 1
(3a - 1)(3a - 1) = 3a.3a - 3a.1 - 1.3a + 1.1 = 9a² - 6a + 1
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás